The crucial role of motivation in the recovery process at inpatient and outpatient substance-related treatment centres - Zwane, Noxolo (Social Work/Maatskaplike Werk, 2025)
For individuals who use substances, compliance and treatment motivation are crucial to the effectiveness of substance-related treatment services. Thus, exploring motivation is imperative to the holistic treatment of individuals who use substances. The intricate interplay between motivation and the decision to seek substance-related treatment among individuals who use substances is conceptualised. Self-determination theory was the most relevant theoretical framework for the study, as it captures the complex, evolving nature of motivation in the treatment process. Document analysis was employed as the primary research methodology for this study, allowing for a systematic review and interpretation of relevant texts to extract meaningful information aligned with the research objectives. This confirms that extrinsic and intrinsic motivation significantly influence the decision to seek substance-related treatment. The researcher argues that the type of motivation a person exhibits prior to being admitted shapes the success of their substance-related treatment regimen. As a result, treatment plans for individuals who use substances need to be tailored accordingly by social workers in substance-related treatment centres. This article contributes to the academic discourse around substance-related treatment and holds practical implications and offers guidelines for treatment centres and healthcare professionals, such as social workers in treatment centres.